2021
DOI: 10.1044/2021_jslhr-21-00084
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency of Atypical and Extreme Values for Pharyngeal Phase Swallowing Measures in Mild Parkinson Disease Compared to Healthy Aging

Abstract: Purpose Dysphagia is thought to be prevalent and a leading cause of morbidity and mortality in people with Parkinson disease (PwPD). The aim of this study was to compare the frequencies of atypical and extreme values for measures of swallowing physiology in PwPD and in an age- and sex-matched cohort of healthy adults. Atypical and extreme values were defined, respectively, as values falling in the 25% and 5% tails of the reference distribution for healthy adults under age 60 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…In PWPD, however, larger volumes were significantly associated with occurrences of airway invasion. PWPD have been shown to take larger than expected bolus sip size on thicker consistencies [ 46 ] and all cup volume trials in this sample were of thickened consistencies. This suggests that the volume of liquid being taken per administration in PWPD, regardless of consistency, significantly elevates the risk of episodes of airway invasion.…”
Section: Discussionmentioning
confidence: 98%
“…In PWPD, however, larger volumes were significantly associated with occurrences of airway invasion. PWPD have been shown to take larger than expected bolus sip size on thicker consistencies [ 46 ] and all cup volume trials in this sample were of thickened consistencies. This suggests that the volume of liquid being taken per administration in PWPD, regardless of consistency, significantly elevates the risk of episodes of airway invasion.…”
Section: Discussionmentioning
confidence: 98%
“…A number of studies have reported prolonged timing measures in PwPD compared to healthy controls, including prolonged swallow reaction time, delay in onset of airway closure, prolonged airway closure duration, prolonged UES opening duration, and delayed relaxation of hyoid elevation after the swallow. 13 , 14 , 15 , 28 On the contrary, Nagaya and colleagues found no differences in stage transition duration, pharyngeal response duration (i.e., duration from initiation of maximal hyoid excursion to the hyoid return to rest), pharyngeal transit duration (i.e., duration from the arrival of the bolus head at the mandibular ramus until the bolus tail passed through the upper esophageal sphincter), duration of UES opening, and total swallow duration (i.e., time from initiation of posterior bolus movement until the bolus tail passed through the UES) when comparing patients with PD to controls, 29 despite the patients having moderate or severe PD (Hoehn &Yahr [H&Y] scale scores of 3–5). 30 …”
Section: Discussionmentioning
confidence: 99%
“…Altered timing has been reported in several studies of swallowing in individuals with neurological conditions including neurodegenerative diseases. 9 , 10 , 11 , 12 , 13 , 14 , 15 These studies have frequently included patients with diverse etiologies (e.g., stroke, acquired brain injury, Parkinson disease [PD], amyotrophic lateral sclerosis [ALS], neuromuscular diseases) and have not explored disease‐specific differences. Given the heterogenous progression and characteristics of these diseases, it may not be appropriate to group these conditions together, and expect common patterns in swallowing.…”
Section: Introductionmentioning
confidence: 99%
“…Several timing metrics pertaining to swallow reaction and laryngeal vestibule closure (LVC) were selected for analysis to better characterize relationships between swallowing safety and MAIP. These metrics were defined and rated in accordance with the Analysis of Swallowing Physiology: Events, Kinematics and Timing (ASPEKT) method decribed in full detail by Steele and colleagues 43 and prior work by Waito, Mancopes, and Gandhi 44–46 . The specific timing metrics for the current study included (1) LVC Duration (amount of time in milliseconds (msec) between LVC onset and laryngeal vestibule opening); (2) Time‐to‐LVC (hyoid burst to onset of LVC in msec); and (3) Swallow Reaction Time (interval between bolus passing ramus of mandible and onset of LVC in msec).…”
Section: Methodsmentioning
confidence: 99%
“…These metrics were defined and rated in accordance with the Analysis of Swallowing Physiology: Events, Kinematics and Timing (ASPEKT) method decribed in full detail by Steele and colleagues 43 and prior work by Waito, Mancopes, and Gandhi. [44][45][46] The specific timing metrics for the current study included (1) LVC Duration (amount of time in milliseconds (msec) between LVC onset and laryngeal vestibule opening); (2) Time-to-LVC (hyoid burst to onset of LVC in msec); and (3) Swallow Reaction Time (interval between bolus passing ramus of mandible and onset of LVC in msec). These timing metrics were analyzed on the first swallow of the 5-ml thin liquid, cup sip liquid, and 5-ml moderately thick bolus trials for a total of nine timing ratings per participant.…”
Section: Swallowing Timingmentioning
confidence: 99%